2022
DOI: 10.3390/ijerph19159107
|View full text |Cite
|
Sign up to set email alerts
|

Revitalization of the Waterfront Park Based on Industrial Heritage Using Post-Occupancy Evaluation—A Case Study of Shanghai (China)

Abstract: With the rapid development of urban construction, the waterfront industrial heritage park has played an active role in shaping the city’s image, regional economic development and environmental improvement, and the continuation of the city’s waterfront history. The waterfront park based on industrial heritage using post-occupancy evaluation will help improve the sustainable management, maintenance, and design level of the project in the future. However, there is insufficient research on the waterfront industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Female users tended to spend less time engaging with urban river corridors (Xie et al, 2023). Two studies from China demonstrated that the proportion of females in the spatial distribution of users is slightly higher than males (Wu et al, 2019b;Zhang et al, 2022b). However, another study conducted in the Riverside area of Barcelona, Spain, came to the opposite conclusion, suggesting that men outnumbered women.…”
Section: Personal Attributesmentioning
confidence: 96%
See 3 more Smart Citations
“…Female users tended to spend less time engaging with urban river corridors (Xie et al, 2023). Two studies from China demonstrated that the proportion of females in the spatial distribution of users is slightly higher than males (Wu et al, 2019b;Zhang et al, 2022b). However, another study conducted in the Riverside area of Barcelona, Spain, came to the opposite conclusion, suggesting that men outnumbered women.…”
Section: Personal Attributesmentioning
confidence: 96%
“…The majority of these studies consistently reported that walking is the predominant mode of transportation for individuals accessing urban river corridors (Gong et al, 2019;Ouyang & Wu,2023;Xie et al, 2023;Zhang et al, 2022;Zhao et al, 2021;Zhou et al, 2022). Other modes of transportation were found, including public transportation, private vehicles, sightseeing buses, and multi-bikes (Liu et al, 2023;Othman et al, 2021;Völker & Kistemann,2013;Zhang et al, 2022b). A study investigating the preferences and attitudes of citizens towards urban riversides revealed that individuals residing farther from the river corridors primarily relied on private vehicles, which may raise concerns regarding traffic connectivity and parking availability (Wang et al, 2020).…”
Section: Personal Attributesmentioning
confidence: 96%
See 2 more Smart Citations
“…However, at this stage, sometimes the landscape effect of urban waterfront green space varies, and the green space with excellent landscape aesthetic value fails to serve the needs of most citizens. This leads to the uneven distribution of public social resources [ 10 , 11 , 12 , 13 , 14 ], the simple pursuit of modernization and standardization of waterfront landscape [ 15 , 16 ], and the intensification of contradictions between different types of land use in waterfront areas [ 17 , 18 , 19 , 20 , 21 , 22 ]. These phenomena are not conducive to China’s development of green ecological civilization construction ideas or China’s common prosperity concept.…”
Section: Introductionmentioning
confidence: 99%